Kesesuaian Habitat Bayi Hiu Karang Sirip Hitam di Taman Nasional Taka Bonerate - Sudono, Chynta Veyra Aulia; Iranawati, Feni; Asri, Asri; Yona, Defri (Universitas Diponegoro, 2025)
Blacktip Reef Sharks (Carcharinus melanopterus) is one of many sharks that are found in Indo-pasific waters and currently listed as vulnerable in IUCN Redlist due to a decrease in population. Habitat suitability and environmental parameters are one of the factors that influence the presence of populations. This research focuses on habitat suitability of Blacktip Reef Sharks pups nursery grounds on the coast of Jinato and Tinabo Besar island, Taka Bonerate National Park with differences in environmental conditions and zone types. Therefore, this research was conducted to analyze the state of environmental parameters at both study site and analyze the influence of parameters and compare the habitat suitability of Blacktip Reef Shark babies at both study site. Data collection was conducted primarily and secondarily in both islands In July and August 2024 and processed using Spearman correlagtion and venn diagram. The number of Blacktip Reef Shark pups on Jinato Island was found to be 3 while on Tinabo Besar Island it was found to be 207, so it is assumed that there is an influence of environmental conditions on the presence of shark pups. There are significant differences and influences on chlorophyll-a, current speed, and salinity parameters, with current being the most influential parameter in the habitat suitability of blacktip reef shark pups on both islands. Tinabo Besar Island has slower current speed conditions, indicating a higher level of habitat suitability. Hiu Karang Sirip Hitam (Carcharinus melanopterus) merupakan salah satu hiu pada area Indo-pasifik yang termasuk kedalam Redlist IUCN dengan kategori vulnerable karena adanya penurunan populasi. Kesesuaian habitat dan parameter lingkungan merupakan salah satu faktor yang memengaruhi keberadaan populasi hiu. Penelitian ini berfokus terhadap kesesuaian habitat bayi Hiu Karang Sirip Hitam di pesisir Pulau Jinato dan Tinabo Besar, Taman Nasional Taka Bonerate dengan perbedaan kondisi lingkungan dan tipe zona yang berbeda. Oleh karena itu, penelitian ini dilakukan untuk menganalisis perbedaan parameter pada kedua pulau, menganalisis pengaruh parameter serta membandingkan kesesuaian habitat bayi Hiu Karang Sirip Hitam pada lokasi kajian. Pengambilan data dilakukan baik secara primer dan sekunder pada kedua pulau di bulan Juli dan Agustus 2024 dan diolah menggunakan uji korelasi Speaman dan diagram venn. Jumlah bayi Hiu Karang Sirip Hitam pada pulau Jinato ditemukan 3 ekor sedangkan pada Pulau Tinabo Besar ditemukan 207 ekor sehingga diasumsikan adanya pengaruh kondisi lingkungan terhadap keberadaan bayi hiu. Terdapat perbedaan dan pengaruh signifikan pada parameter klorofil-a, arus, dan salinitas dengan paremter arus sebagai paremter yang paling berpegaruh dalam kesesuaian habitat bayi Hiu Karang Sirip Hitam di kedua pulau. Pulau Tinabo Besar memiliki kondisi arus yang lebih rendah sehingga menujukkan tingkat kesesuaian habitat yang lebih tinggi.